Fluoride-Salt-Cooled High-Temperature Reactor (FHR) Using British Advanced Gas-Cooled Reactor (AGR) Refueling Technology and Decay Heat Removal Systems That Prevent Salt Freezing. (2nd September 2019) - Forsberg, Charles; Wang, Dean; Shwageraus, Eugene; Mays, Brian; Parks, Geoff; Coyle, Carolyn; Liu, Maolong
Abstract: The flouride-salt-cooled high-temperature reactor (FHR) uses graphite-matrix coated-particle fuel [the same as high-temperature gas-cooled reactors (HTGRs)] and a clean liquid salt coolant. It delivers heat to the industrial process or the power cycle at temperatures between 600°C and 700°C with average heat delivery temperatures higher than for other reactors. The melting point of the liquid salt coolant is above 450°C. The high minimum temperatures present refueling challenges and require special features to control temperatures, avoiding excessively high temperatures and freezing of the coolant that could impact decay heat cooling systems. This paper describes a preconceptual FHR design that addresses many of these challenges by adopting features from the British advanced gas-cooled reactor (AGR) and alternative decay heat cooling systems. The bases for specific design choices are described. The AGRs are carbon dioxide–cooled and graphite-moderated reactors that use cylindrical fuel subassemblies with vertical refueling at 650°C, which meets the FHR high-temperature refueling requirements. Fourteen AGRs have operated for many decades. The AGR uses eight cylindrical fuel subassemblies, each 1 m tall coupled axially together by a metal stringer to create a long fuel assembly. The stringer assemblies are in vertical channels in a graphite core that provides neutron moderation. This geometric core design is compatible with an FHR using graphite-matrix coated-particle fuel. The FHR uses a once-through fuel cycle. The design minimizes used nuclear fuel volumes relative to other FHR and HTGR designs. The primary system is inside a secondary liquid salt–filled tank that (1) provides an added heat sink for decay heat, (2) helps to ensure no freezing of primary system salt, and (3) helps to ensure no major fuel failures in a beyond-design-basis accident. The refueling standpipes above each stringer fuel assembly in the AGR core with modifications can be used in an FHR for refueling and can provide efficient heat transfer between the primary system and the secondary liquid salt–filled tank. The passive decay heat removal system uses heat pipes that turn on and off at a preset temperature to avoid overheating the core in a reactor accident and to avoid freezing the salt coolant as decay heat decreases after reactor shutdown.